2020
DOI: 10.1002/adfm.202008244
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible‐Light Driven Photothermal Conversion of CO2 to Methane by Nickel Nanoparticles Supported on Barium Titanate

Abstract: Solar‐driven methanation represents a potentially cost‐efficient and environmentally friendly route for the direct hydrogenation of CO2. Recently, photothermal catalysis, which involves the combination of both photochemical and thermochemical pathways, has emerged as a promising strategy for the production of solar fuels. For a photothermal catalyst to efficiently convert CO2 under illumination, in the absence of external heating, effective light harvesting, an excellent photothermal conversion and efficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 51 publications
3
61
0
Order By: Relevance
“…These observations can be explained by the analysis of the thermal and optical properties of Al 2 O 3 , namely its high thermal conductivity (30 W m −1 K −1 ) and bandgap (7.6 eV) that make this material a poor thermal insulator and photoactive support [37] . For these reasons, the photo‐thermal performance of Pd(0.5)−Al 2 O 3 photocatalyst is substantially less efficient than in the case of Pd(0.5)‐BTO, as previously observed in related precedents [25b] . Interestingly, based on these experiments we also observed that product distribution was certainly influenced by the nature of the support.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These observations can be explained by the analysis of the thermal and optical properties of Al 2 O 3 , namely its high thermal conductivity (30 W m −1 K −1 ) and bandgap (7.6 eV) that make this material a poor thermal insulator and photoactive support [37] . For these reasons, the photo‐thermal performance of Pd(0.5)−Al 2 O 3 photocatalyst is substantially less efficient than in the case of Pd(0.5)‐BTO, as previously observed in related precedents [25b] . Interestingly, based on these experiments we also observed that product distribution was certainly influenced by the nature of the support.…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, the emission intensity of the sample containing Pd decreased in comparison to that of pristine BTO, which could be attributed to the electron or/and energy transfer from BTO to Pd NPs. Figure S9b shows the band‐alignment energy diagram with the conduction and valence band potentials of BTO and the Fermi level of Pd [25b,28] . Upon contact between both the semiconductor and the metal, the higher work function of Pd compared to BTO favors the formation of a Schottky barrier at the Pd‐BTO interface.…”
Section: Resultsmentioning
confidence: 99%
“…Upon Ni addition and pretreatment, the light absorbance extends from the UV region into the visible and near infrared. The absorbance in the Vis and NIR regions can be attributed to the presence of metallic Ni deposits, consistent with group VIII metals [ 35 ]. Specifically, the broadband absorbance is driven by intraband transition within overlaid partially filled 3d sub-orbitals [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, photothermal catalytic reactions on supported metal catalysts have been reported, [58][59][60] where the light energy absorbed by metal nanoparticles is converted to thermal energy to promote the catalysis on the metal catalyst. Thus, reaction tests in the dark were carried out with the Au(0.4)/TiO 2 sample at various temperatures in a flow of ethane with Ar carrier gas to study the effect of thermal energy on the reaction.…”
Section: Effect Of Thermal Energymentioning
confidence: 99%